Jurisprudence and Teacher’s Ethics: Companionship or Succession - Seyyed Naqi Mosavi (تربیت اسلامی, 2022)
The literature of professional ethics is increasing. It is broken through the boundaries of education, and categories such as teacher’s professional ethics are derived from it; therefore, it is necessary to attempt to localize this literature. On the other hand, educational jurisprudence is developing as a new field in education, so it is necessary to have a specialized approach to teachers and teacher training. The ratio of teacher’s ethics to teacher’s jurisprudence is necessary in research (science production) and education (educational program and curriculum) and this is the main issue of this paper. this study, through a descriptive and analytical method, explaining what the teacher’s jurisprudence and teacher’s ethics are, has determined the ratio between them and come to a conclusion that these two fields of study, while different, are closely related to each other, and in the position of research, (Islamic) teacher’s ethics can rely on teacher’s jurisprudence and submit to its methodology of Ijtihad so that a comprehensive system of teacher’s rules, manners, and ethics can be deduced systematically. At the end of paper, teacher’s ethics in the teacher training curriculum has been evaluated, and some suggestions have been offered.